PHYSICAL CHARACTERISTICS, SENSORY EVALUATION, AND AMINO ACID CONTENT OF POWDERED OVER FERMENTED MLANDING TEMPEH - Asri Nursiwi; Dwi Ishartani; Ardhea Mustika Sari; Nur Ayu Istiqomah (Jurnal Teknologi dan Industri Pangan, 2021)
Mlanding tempeh is a non-soybean tempeh which made from ripe lamtoro (Leucaena leucocephala) seed. In Wonogiri, an area in Indonesia over fermented mlanding tempeh (OFMT) often used as seasoning for traditional food because it produced special taste. OFMT is dried to extend the shelf life. The objectives of the research was to study the physical characteristics, sensory evaluation, and amino acid content of powdered over fermented mlanding tempeh (POFMT). The drying of the OFMT used a cabinet dryer with the drying temperature were 55, 60, and 65°C for 8 hours then ground into powder. The powder was analyzed for yield, water absorption capacity, solubility, bulk density, hedonic test, and amino acid content. The results showed that the different drying temperature had a significant effect on yield and water absorption capacity but had not significant effect on solubility and bulk density of the POFMT. The yied varies between 7.06-12.92% and the water absrption capacity varies between 0.36-0.55 g/g. While the solubility of the POFMT varies between 36.45-41.33% and the bulk density varies between 0.38-0.42 g/mL. The different drying temperature had not a significant effect on panelist’s preference. Amino acid content of POFMT varies between 0.99-5.43% (db), with the two highest content is glutamic acid and aspartic acid.